The impact of existing and modify wrestling shoes on foot posture deformities in 12-13 years old athletes - Coskuner, Zeki; Acak, Mahmut; Buyukcelebi, Hakan; Ozen, Gokmen; Kurak, Kemal (Iermakov S S, 2022)
Background and Study Aim In the early years when sports footwear became compulsory, the importance of shoe design was not considered in terms of athletes' health. Since the early years of wrestling shoe use, these gears have been manufactured according to the rules of competition, and modifications have been very limited. In this regard, this study aims to determine the effect of existing wrestling shoes on foot deformation. Material and Methods The study was carried out with the participation of 108 young male athletes who had the same training on the same ground for three years in the Wrestling Training Center. The athletes were divided into two groups, an experimental and a control group. While the control group wore wrestling shoes produced by widely used brands, the experimental group wore newly designed wrestling shoes. Foot arch values and images of both groups were determined using a podoscope device at the beginning and end of the study. The evaluations were made according to the Staheli arch index. Results The results of the statistical analysis revealed that differences were found in the footprint measurement values of the control group. It was determined that this difference in the footprints was greater among the freestyle wrestlers. The decrease in the averages between the first and second measurement values of the group using the newly designed wrestling shoes was found to be highly positive and in a linear direction. Also, it was determined that the pain score values of the control group were higher than the scores of the experimental group after training. Conclusions The results revealed that there were deformations in the feet of the control group wrestlers wearing available wrestling shoes. It was observed that freestyle wrestling athletes had more deformation than Greco-Roman style wrestlers, and leg pains were more prevalent after training and competitions. Based on these results, it was concluded that the design of wrestling shoes produced with today's technology needs to be redesigned.
Keywords: wrestling; athlete health; sports shoes; wrestling shoes; flatfoot; leg pain